Metachronous malignancies in head and neck region: Report of two cases - Sushma Yalavarthi; Pramod Kumar Pamu; Mallesh Thoondla; Saloni Gupta (Wolters Kluwer Medknow Publications, 2014)
The development of a second primary cancer after treatment of the first with radiotherapy or chemotherapy is well documented. Multiple metachronous primary cancers are known to occur in an individual, but it is often seen with hematological malignancies of childhood. The prevalence of multiple primary malignancies (MPM) is between 0.73% and 11.7%. The most frequent malignant associations are ovary-colon, ovary-breast, and breast-breast. The possibility of developing a second metachronous cancer 5 years after undergoing treatment of the initial head and neck cancer is approximately 22%. Here, we report two cases of multiple metachronous malignancies in head and neck region. A 46-year-old woman presented with thyroid and salivary gland neoplasms metachronously and another 21-year-old woman with Hodgkin' s Lymphoma, mucoepidermoid carcinoma of salivary Gland, and follicular variant of papillary carcinoma of thyroid.